Estudio de prefactibilidad para la instalación de una planta productora de barras proteicas en base a cushuro (nostoc sphaericum) - Espantoso Aguirre, Marco Antonio (2023)
The protein bar based on Cushuro (Nostoc Sphaericum) is a product for mass consumption whose main benefit is the high content of proteins, iron, calcium, potassium, B1, B2, B5 and B8 which is a super food which helps to muscle recovery as well as being anti-anemic and strengthening the immune system. The purpose of this pre-feasibility study is to demonstrate that the project has the market, technological, economic-financial and social viability of a plant that produces and markets protein bars based on Cushuro in 100 grams presentation. The proposal of this business is based on having a purchase intention of 58.50% (the survey was carried out in Metropolitan Lima in sectors A and B from 18 to 45 years), which allows knowing the demand for the first year 72 814 in kilograms to a demand of 76 071 kilograms in the last estimated year For the location of the plant, construction in Metropolitan Lima (Macro location) in the district of Lurin was determined as the best option due to compliance with the factors necessary for the operation of the industrial plant such as the supply of water, energy, raw materials, proximity to the market and citizen security index. In addition, a plant layout of 924 m2 with an installed capacity of 1 965 600 Cushuro bars of 100 grams per year was calculated thanks to the technology necessary for production. The evaluation obtained an economic VAN of s / 2 499 307 for the 5-year useful life of the project, an TIR of 61% higher than the COK of 19,05%. Similarly, the project is viable through financing 50% of the investment, obtaining a financial VAN of s / 2 583 539, an TIR of 95% higher than the COK of 19,05%.